The Physiologic Mechanisms of Paced QRS Narrowing During Left Bundle Branch Pacing in Right Bundle Branch Block Patients - Zhu, Kailun; Sun, Yali; Lin, Manxin; Deng, Yingjian; Li, Linlin; Li, Guiyang; Liu, Jianghai; Wan, Xingcai; Chang, Dong; Li, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Left bundle branch pacing (LBBP) is a physiological pacing technique that captures the left bundle branch (LBB) directly, causing the left ventricle (LV) to be excited earlier than the right ventricle (RV), resulting in a “iatrogenic” right bundle branch block (RBBB) pacing pattern. Several studies have recently shown that permanent LBBP can completely or partially narrow the wide QRS duration of the intrinsic RBBB in most patients with bradycardia, although the mechanisms by which this occurs has not been thoroughly investigated. This article presents a review of the LBBP in patients with intrinsic RBBB mentioned in current case reports and clinical studies, discussing the technique, possible mechanisms, future clinical explorations, and the feasibility of eliminating the interventricular dyssynchronization accompanied with LBBP.